Atomistic study on the super-elasticity of nanocrystalline NiTi shape memory alloy subjected to a cyclic deformation - Wang, Bing (2020)
By establishing some atomistic simulation cells with the same size but different numbers of grains, molecular dynamics simulations are performed to investigate the super-elasticity of nanocrystalline NiTi shape memory alloy subjected to a cyclic tension-unloading and its dependence on the grain size. The effect of grain boundaries on the martensite transformation stress as well as the nucleation and growth of martensite phase is addressed. The degeneration of super-elasticity and the initiation and growth of defects in the nanocrystalline NiTi SMA during the cyclic tension-unloading are discussed. The results show that the super-elasticity degeneration occurs during the cyclic deformation of nanocrystalline NiTi SMA, and the residual strain accumulates progressively with the increasing number of cycles, which becomes more significant with the decrease of grain size. The grain boundaries can enhance the martensite transformation stress of nanocrystalline NiTi SMA and suppress the instability occurred during the martensite transformation. It is revealed that the interstitial atoms and plastic deformation are mainly concentrated within the grain boundaries.